Influence factors in change methods choice and their impact on change deficiencies: A case study of construction industry in transition economy - Roberto Biloslavo; Peter Friedl (Journal for East European Management Studies, 2009)
The basic purpose of this research is to examine if influence factors in change methods choice are linked to an inappropriate approach (i.e. deficiencies) towards change. A combination of qualitative and quantitative approaches to research work was applied. The data were obtained by a semi-structured interview together a questionnaire, and then processed using the method of factor analysis and multiple regression. Based on research findings we can conclude that between the factors of choice of change methods and deficiencies in the implementation of change taken as a whole, there is no direct link. However, two dimensions of the factors in the choice of method of change have a positive influence on deficiencies arising during the implementation of change. – – Der Hauptzweck dieser Untersuchung ist es zu überprüfen, ob die Einflussfaktoren auf die Wahl der Methoden des Wandels mit einer ungemessenen Einstellung (bzw. Defiziten) gegenüber dem Wandel in Zusammenhang stehen. Eine Kombination aus qualitativen und quantitativen Forschungsansätzen wurde verwendet. Die Daten wurden durch halbstrukturierte Interviews und Fragebogen gewonnen, und dann mithilfe von Faktorenanalyse und Mehrfachregression verarbeitet. Basierend auf den Forschungsergebnissen können wir feststellen, dass es keinen direkten Zusammenhang zwischen der Wahl von Methoden des Wandels und den Defiziten in der Durchführung von Wandel als Ganzes gibt. Jedoch haben zwei Dimensionen der Methodenwahl einen positiven Einfluss auf Defizite, die bei der Durchführung des Wandels entstehen.
Keywords: 650; Change management; management; change methods